Perancangan Motion Graphic Pengolahan Sampah 3R Pada Kampung Edukasi Sampah Sidoarjo - Puri Dewanggi, Amisha Nindi; Setiawan, Bayu; Nisa, Diana Aqidatun (Peneliti.net, 2024)
The phenomenon of unmanaged waste generation due to lack of public awareness requires effective education methods, especially from an early age. For this reason, a motion graphic-based educational media was designed which can provide interesting, educative and informative information to elementary school students when visiting the Garbage Education Village. This motion graphic media will include a basic explanation of types of waste, an explanation of 3R waste processing, steps for waste processing, as well as the causes and consequences of waste management. The aim of this media is to increase awareness and help children understand the importance of waste management through a fun and interesting approach. The research method used to design this media includes qualitative and quantitative analysis by collecting primary data through interviews and observations with interested parties such as the Head of the RT Kampung Edukasi Sampah, elementary school students who visited the place, and motion graphics experts. Apart from that, secondary data from literature studies was also used. Quantitative methods are also used by compiling questionnaires to collect data which is analyzed to identify suitable design ideas. In designing this motion graphic, using simple Indonesian language and a bright pastel color palette were chosen to arouse children's interest. Attractive characters are also used to reinforce aspects of the design that appeal to children. It is hoped that with this motion graphic media, the message about the importance of good waste management can be conveyed effectively and informatively to elementary school students in grades 4 to 6 or the equivalent of ages 9 to 12 years, so that they learn better environmental awareness and can play an active role in reducing waste generation in Indonesia.